Domestic Violence Between Childhood Incest and Re-victimization: A Study Among Anti-violence Centers in Italy - Testoni, Ines; Mariani, Chiara; Zamperini, Adriano (Frontiers in Psychology, 2018)
The study focuses on a specific problem in the area of child sexual abuse (CSA), which is still under-researched: the relationship between incest and adult female re-victimization treatment within the ambit of domestic violence in Italian centers. About 112 anti-violence centers were contacted, but only 13 participated and only 16 psychologists were interviewed to reconstruct the biographies of 32 victims. The study aimed to examine if and how the service centers recognized and dealt with the problem of re-victimization among survivors based on psychologists’ narrations. Findings showed that the description of perpetrators revealed not only sexual abuse was perpetrated, but also psychological and physical abuse. About half of mothers did not come to their daughters’ aid and those who cooperated with the abusers had mostly suffered from CSA at a time in their life. Only three mothers did help their daughters in contacting the anti-violence centers. However, most of the service centers were not concerned with the relationship between incest and domestic re-victimization, while those who considered the problem, dealt with it only on the practitioner–patient level. In addition, despite the psychologists used professional and empathetic language, they disclosed their high emotional involvement and a genuine bewilderment. A discussion on the need to standardize the psychotherapeutic support given to these re-victimized women was presented, with a critique to the un-discriminated de-pathologization approach adopted by almost all anti-violence centers. In particular, we wanted to underline the fact that, although, this approach is useful in treating victims who were not abused during infancy, it could be insufficient for women who suffered from incest.